PERBANDINGAN PERTUMBUHAN IKAN LELE SANGKURIANG (Clarias sp) ANTARA PEMBERIAN PAKAN CACING SUTRA DENGAN PAKAN PELET SEBAGAI SUMBER BELAJAR BIOLOGI - Krisnando, Yuda; Sujarwanta, Agus (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
The purpose of the research were to determine differences in seed growth sangkuriang catfish (Clarias sp) between feeding silk worms (Tubifex) with feed pellets ando determine which of the treatments produced seed growth sangkuriang catfish (Clarias sp) the greater of feeding silk worms (Tubifex) and feed pellets. The research was conducted in Â Iringmulyo Metro East, Metro City, on July 21 until August 19, 2013. Samples at each of the two treatments was 50 sangkuriang fry catfish (Clarias sp). Data were analyzed by using the formula t test to analysis the equality of two on average. To test the equality of two average gained 8.5 thit > tdaf 2.00 at significance level Î± = 0.05, so thit > tdaf, then reject H0, which means there is a real difference in the growth of the seed length sangkuriang catfish (Clarias sp) between nutrients obtained from food hair worms (Tubifex) with feed pellets. Sangkuriang seed catfish (Clarias sp) with a source of nutrients feed hair worms (Tubifex) with a source of nutrients feed pellets can be used as an alternative learning objects on the growth and development material. Kata kunci: cacing sutra, pelet, pertumbuhan lele sangkuriang.